Margaret Fuller, critic : writings from the New-York Tribune, 1844-1846 - Bean, Judith Mattson; Myerson, Joel (Columbia University Press, 2000)
Ardent feminist, leader of the transcendentalist movement, participant in the European revolutions of 1848-49, and an inspiration for Zenobia in Hawthorne's Blithedale Romance and the caricature Miranda in James Russell Lowell's Fable for Critics, Margaret Fuller was one of the most influential personalities of her day. Though a plethora of critical writings, biographies, and bibliographies on Fuller have been available-as well as her three published books, European dispatches, and editions of her letters and journals-until now there has been no complete, reliable edition of her writings from the New-York Tribune, where she was the first literary editor. Fuller wrote 250 articles for the Tribune, only 38 of which have been reprinted in modern editions; this book makes this significant portion of her writings available to the public for the first time. Judith Mattson Bean and Joel Myerson have assembled a selection of Fuller's essays and reviews on American and British literature, music, culture and politics, and art. The accompanying fully annotated, searchable CD-ROM contains all of Fuller's New-York Tribune writings.